A Contextualização na Modelagem Matemática na Educação Matemática - Schwendler, Denise (2023)
The term contextualization has frequently been mentioned in literature within discourses related to teaching practices, providing the articulation of mathematical content with applied situations and aiming to awaken students' interest in learning. Contextualization as a way of attributing direction and meanings was highlighted in official Brazilian documents, and research in Mathematics Education gathered with them. However, these statements are taken in their immediacy, without further reflection, therefore, in a philosophical approach, in a naive way, without explanations. The same happens in Mathematical Modeling, which, according to authors in the area, contextualization is often improperly assumed, thus emerging the need for studies that contribute to the understanding of this aspect. Considering these arguments and the experience with the subject, we express the following research question: what is this, the contextualization in Mathematical Modeling in Mathematics Education? In this way, the phenomenon of contextualization in Mathematical Modeling is questioned under the phenomenological and hermeneutic posture. The way to go to the phenomenon requested the understanding of texts that focused on it. So, we used the texts of scientific communications and experience reports from the annals of the National Conference about Modeling in Mathematics Education from 1999 to 2019. From 591 works available, 533 were significant for the investigation, as they contained, in the text body, at least some of the terms relevant to the investigation: contextualization and context. From the analysis of the phenomenon structure, four categories emerged: 1) The context is part of the Modeling; 2) The context as a ground in which... 3) The contextualization as a way of, that and for; 4) Modeling as a way of contextualizing or contextualizing through Modeling. The analysis took place in a hermeneutic phenomenological interpretative movement, which allows targeting aspects that, at first sight, are not explicit. From the categories interpretation, the context can be assumed from different perspectives, considered as an origin, as something that influences and interferes in Mathematical Modeling and is represented by/with it. The types of contexts, such as everyday life, reality, interdisciplinarity, assumed as solo, are shown with aspects that indicate the psychologization of the context in Modeling. Contextualization, in the other hand, emerged as a way of, that and for, which deal with the actions of subjects, purposes, objectives and paths. From this investigation, we understand that contextualization takes place in human historicity, showing a different direction from that which is usual within the community.